Lead exposure induces nitrative stress and disrupts ribbon synapses in the cochlea - Rosati, Rita; Birbeck, Johnna A.; Westrick, Judy; Jamesdaniel, Samson (Frontiers in Molecular Neuroscience, 2022)
Environmental exposure to heavy metal lead, a public health hazard in many post-industrial cities, causes hearing impairment upon long-term exposure. Lead-induced cochlear and vestibular dysfunction is well-documented in animal models. Although short-term exposure to lead at concentrations relevant to environmental settings does not cause significant shifts in hearing thresholds in adults, moderate- to low-level lead exposures induce neuronal damage and synaptic dysfunction. We reported that lead exposure induces oxidative stress in the mouse cochlea. However, lead-induced nitrative stress and potential damage to cochlear ribbon synapses are yet to be fully understood. Therefore, this study has evaluated cochlear synaptopathy and nitrative stress in young-adult mice exposed to 2 mM lead acetate for 28 days. Inductively coupled plasma mass spectrometry (ICP-MS) analysis indicated that this exposure significantly increased the blood lead levels. Assessment of hair cell loss by immunohistochemistry analysis and outer hair cell (OHC) activity by recording distortion product otoacoustic emissions (DPOAEs) indicated that the structure and function of the hair cells were not affected by lead exposure. However, this exposure significantly decreased the expression of C-terminal-binding protein-2 (CtBP2) and GluA2, pre- and post-synaptic protein markers in the inner hair cell synapses, particularly in the basal turn of the organ of Corti, suggesting lead-induced disruption of ribbon synapses. In addition, lead exposure significantly increased the nitrotyrosine levels in spiral ganglion cells, suggesting lead-induced nitrative stress in the cochlea. Collectively, these findings suggest that lead exposure even at levels that do not affect the OHCs induces cochlear nitrative stress and causes cochlear synaptopathy.